The aesthetics of design shape of the interior spaces for the syndicate of physicians: ريم باسل نوري (Al-Academy, 2016)
The research dealt with the topic ' the aesthetics of design shape of interior spaces for the syndicate of physicians' as it reflects visions evolving to the level of tasting and positive interpretation for the space of work to be on a high design level.The research consisting of four chapters as follow; The first chapter examined the problem of the research contracted in the following question: Have the design shapes any role in achieving and showing the aesthetic side for the syndicate of physicians? so the goal of the research was showing the aesthetics of design shape of interior spaces for the syndicate of physicians, The chapter also included the objective spatial and temporal limits of research .Finally the terms were specified. The second chapter was represented by the theoretical frame that the research depended upon it to elicit indications for the research.The chapter consisted of two parts : the first one dealt with the aesthetics of design shape and their implications in the Interior space ; while the second part dealt with the aesthetic requirements of design shape of the Interior space. The third chapter contained the procedures and methodology of research .It adopted the analytical and descriptive methodology : it depended on the form of analytical axes as an instrument for the research in addition to describing and analysis two purposeful samples .By that way the research got findings ,conclusions, recommendations and general and design suggestions which represented the fourth chapter. The research also contained figures and photographs for the samples and list of references and appendices